SUBSTANTIATION OF THE INDICATORS OF THE ANTHROPOGENIC LOAD AS WELL AS TRANSFORMATION OF ZAPOROZHZHIA REGION LANDSCAPES: (UKRAINE) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The article presents the results of calculations and analysis of the anthropogenic transformation and the landscapes load of Zaporizhizhia Region. Calculation of the coefficient of the anthropogenic transformation allowed classifying the landscape areas in a highly transformed with an average coefficient in the administrative area 6.6. Within the landscape areas, the degree of the anthropogenic load varies from 0.132 to 0.429 units that is one of the highest in Ukraine.
Keywords: anthropogenic landscapes; regional nature management; ecology and landscape analysis; agrarian load; anthropogenic transformation